Effects of orthodontic tooth extrusion produced by different techniques, on the periodontal tissues: a histological study in dogs - da Silva, Vanessa Camila (2020)
Objective: The aim of this study was to compare the periodontal tissue changes resulting from different methods of orthodontic tooth extrusion in dogs. Materials and methods: Notches were surgically prepared in the root surface at the bone crest level of the first premolars of mongrel dogs. After 37 days, extrusion of the first lower and upper premolars was randomly performed by 3 different methods: conventional orthodontic extrusion (OE); open flap debridement performed immediately before orthodontic extrusion (OF); and orthodontic extrusion associated with weekly fiberotomy and scaling (FS). For all groups, extrusion was performed for 21 days followed by one-month retention and sacrifice. Periodontal parameters, descriptive histology, and histomorphometric analyses were performed at the end of the experimental period. Results: The median extrusion was 2.25 in the fiberotomy group, 2.0 mm in the open flap group and 1.0 mm in the orthodontic extrusion group with no significant differences between groups. The highest distance between reference notch and bone crest was observed in the fiberotomy group (p < 0.05). Histologically, radicular resorption repaired with cellular cementum was detected in all groups. Conclusions: Tooth extrusion was successfully achieved with all of the different methods of orthodontic tooth extrusion with no statistical significance between techniques. The fiberotomy approach was effective in avoiding coronal displacement of periodontal tissues. Fiberotomy associated with scaling should be indicated if the objective of the treatment is extrusion without periodontal tissue displacement.